2011
DOI: 10.1007/s12250-011-3182-0
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic fever with renal syndrome complicated by orchitis

Abstract: Hemorrhagic fever with renal syndrome (HFRS) is a disease caused by viruses of the family Bunyaviridae, genus Hantavirus. HFRS from Dobrava virus (DOBV) is a seldom reported disease in Albania. Clinically HFRS is manifested as mild, moderate, or severe. Therefore, the number of cases of Hantavirus' infection may be underestimated, and should be included in the differential diagnosis of many acute infections, hematologic diseases, acute abdominal diseases and renal diseases complicated by acute renal failure. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…11,12 Orchiepididymitis is a very rare complication of HFRS by HNTV/ Dobrava virus infection. 4,13 Other authors such as Eun S Kang, Bui-Mansfield and Bren et al are also suggested by implication of pancreas during HFRS course. [13][14][15] The maternal and fetal outcomes of pregnancy complicated by HFRS have also been reported in China, where the most severe form of HFRS caused by Hantan virus occurs.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…11,12 Orchiepididymitis is a very rare complication of HFRS by HNTV/ Dobrava virus infection. 4,13 Other authors such as Eun S Kang, Bui-Mansfield and Bren et al are also suggested by implication of pancreas during HFRS course. [13][14][15] The maternal and fetal outcomes of pregnancy complicated by HFRS have also been reported in China, where the most severe form of HFRS caused by Hantan virus occurs.…”
Section: Introductionmentioning
confidence: 93%
“…2,8 Neurological, cardiopulmonary hematologic, gastrointestinal, urogenital, ocular and pregnancy complications are prescribe in now days. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The clinical presentation of many patients included typical symptoms of viral encephalitis and several patients developed serious CNS-related complications. 11,12 Orchiepididymitis is a very rare complication of HFRS by HNTV/ Dobrava virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to fever and myalgias, early symptoms include headache, chills, dizziness, nonproductive cough, nausea, vomiting, and other gastrointestinal symptoms. Malaise, diarrhea, and lightheadedness are reported by approximately half of all patients, with less frequent reports of arthralgia, back pain, and abdominal pain [1]. Conjunctival, cerebral, and gastrointestinal (GI) hemorrhages occur in about one-third of patients [4].…”
Section: Discussionmentioning
confidence: 99%
“…e basic pathologic and pathophysiologic disorder in HFRS is capillary damage (vasculitis) [12]. Increased vascular permeability and decreased platelet count are the hallmarks of hantavirus-associated diseases [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation